Economic Development Strategy Through Entrepreneurial Support: Case Study of Morocco - Farissi, Aicha; Roudab, Noureddine (International Journal of Supply Chain Management, 2025)
This research delves deeply into the socioeconomic indicators and targeted population categories within the framework of the Jerada support fund management project, offering valuable insights into the unique challenges and opportunities in the region. The study goes beyond theoretical analysis by proposing practical solutions to Jerada's socioeconomic challenges, providing tangible and real-life responses. As a replicable model, this case study presents concrete and adaptable solutions, demonstrating how research can be translated into actionable strategies. Not only does this study inform the specific context of Jerada, but it also serves as a valuable model for similar territorial development initiatives in Morocco and beyond.